2016
DOI: 10.1186/s40064-016-3078-4
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of balloon-expandable stent in symptomatic stenosis of middle cerebral artery

Abstract: BackgroundStent placement for middle cerebral artery (MCA) stenosis remains a technical and clinical challenge. Our purpose was to assess the safety and feasibility of balloon-expandable stent (BES) for patients with symptomatic M1 stenosis of MCA, and to introduce our experience during the procedure.MethodsIn the study, we analyzed retrospectively 37 patients with M1 stenosis of the MCA ranged from 70 to 90 % in diameter reduction and refractory to medical therapy between January 2012 and January 2015. All th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…However, few studies have investigated the long-term outcomes after balloon-mounted stenting for symptomatic ICAS with experienced interventionalists and proper patient selection. 17 18 The 1-year rates of any stroke, ischemic stroke, hemorrhagic stroke, and death were 8.5%, 8.5%, 0%, and 1.6% in the WOVEN study, and comparable values were found using balloon-mounted stents in the present study. 13 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, few studies have investigated the long-term outcomes after balloon-mounted stenting for symptomatic ICAS with experienced interventionalists and proper patient selection. 17 18 The 1-year rates of any stroke, ischemic stroke, hemorrhagic stroke, and death were 8.5%, 8.5%, 0%, and 1.6% in the WOVEN study, and comparable values were found using balloon-mounted stents in the present study. 13 …”
Section: Discussionsupporting
confidence: 84%
“…11 The Apollo stent (MicroPort Neuro Tech, Shanghai, China) is a balloon-mounted stent with a metallic surface area of about 14.0%, approved by the Chinese Food and Drug Administration for use in patients with symptomatic ICAS. Although several case series have supported its safety and efficacy since 2003, [14][15][16][17][18] a prospective multicenter registry study has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports of its intracranial use for middle cerebral artery (MCA) stenosis or ICA stenosis, including drug-eluting stents (DES). [17][18][19] However, if these stents can be successfully used for MCA and intracranial ICA, it is clear that they can also be used for more proximal extracranial ICAs. As such, BECo stents should be considered as an option for CAS procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Although in several studies balloon angioplasty was done prior to stenting in the SES group, BMS is more effective in reducing the stenosis of arteries. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Details of meta-analysis have been demonstrated in appendix 1.…”
Section: Changes In the Degree Of Stenosismentioning
confidence: 99%